Oldest fruits of the grape family (Vitaceae) from the Late Cretaceous Deccan Cherts of India1. Issue 9 (1st September 2013) - Manchester, Steven R.; Kapgate, Dashrath K.; Wen, Jun
Abstract : Premise of the study: Despite the inferred Cretaceous origin of the Vitaceae, fossils of the grape family are relatively young, with the oldest previously known examples limited to the Paleocene of Europe and North America. New fossil evidence indicates that the family was already present in India in the Late Cretaceous (Maastrichtian), about 10‐15 million years before the tectonic collision of India with Eurasia. Methods: Fruits and seeds were investigated by serial sections and peels of chert from the Deccan Intertrappean beds of central India, and compared anatomically with those of extant genera. Key results: Indovitis chitaleyae gen. et sp. n. is described based on immature fruits bearing four to six seeds, and isolated mature seeds. The seeds possess paired ventral infolds and a dorsal chalaza, features diagnostic of the order Vitales. Characters of chalaza shape, infold morphology, and seed coat anatomy place I. chitaleyae within Vitaceae and favor a phylogenetic position either sister to the Vitis‐Ampelocissus clade or sister to the Ampelopsis‐Clematicissus‐Rhoicissus clade. Conclusions: Presence of the oldest known vitaceous fossils in the latest Cretaceous of India indicates a previously undocumented Gondwanan history and a possible southern hemisphere origin for the Vitales. An "out‐of‐India" scenario might explain the relatively sudden appearance of diverse Vitaceae in the Late Paleocene and Early Eocene of the Northern Hemisphere.